The Effect of Recognition of Social Disasters on School Life Satisfaction of the Adolescent: The Sequential Mediating Effect of Depression and Smartphone Dependency - 차한솔 (Korean Journal of Social Quality, 2023)
The purpose of this study is to verify the sequential mediating effect of depression and smartphone dependency on the effect of recognition of disasters on school life satisfaction of the adolescents. For the present study, a dataset taken from the 3th survey of the Korean Children & Youth Panel Survey (2018) was conducted using the SPSS PROCESS MACRO Model 6 developed by Hayes (2013). The results of this study are as follows. First, depression and smartphone dependency had a significant negative effect on school life satisfaction, while recognition of social disasters had no significant direct effect on school life satisfaction. Second, depression and smartphone dependency mediated the relationship between recognition of social disasters and school life satisfaction. Third, depression and smartphone dependency showed sequential mediating effects in the relationship between recognition of social disasters and school life satisfaction. Through this, it was verified that the higher the recognition of social disasters, the lower the depression, and the lower the smartphone dependency, and the higher the school life satisfaction. Therefore, based on the results of this study, suggestions for improving the recognition of social disasters and school life satisfaction of adolescents were proposed. KCI Citation Count: 0